ANALYSIS OF POTENTIAL EARTHQUAKE HAZARDS ON PALEMBANG CITY - SUMATERA ISLAND - YAHD XANGGAM (NIM: 12313034), ZAEL
Indonesia is a country that is often struck by earthquakes because Indonesia located at the confluence of three continental plates namely the Indo-Australian, Eurasian and Pacific plates. Earthquakes in Indonesia, especially those originating from megathrust and land quaternary active faults, have caused a lot of losses, both in terms of material and lives. Earthquakes do not kill directly, but buildings caused by earthquakes are the ones that can kill. Therefore, the strength of building construction should be designed taking into account the estimated acceleration of land movements due to earthquakes in each region. The way to determine the potential for earthquake shocks is to analyze the potential curve for earthquake hazard or hazard function. In this final project, an estimation and analysis of the earthquake hazard potential curve in the city of Palembang against several megathrust points was carried out. Determination of the earthquake hazard potential curve is carried out by plotting the values of earthquake events and Peak Ground Acceleration. In this study, estimating several megathrust source points for Palembang City, the total and geometric probability of the Peak Ground Acceleration estimation results can be calculated. Based on the results of the potential hazard curve, it can be noted that there is a tendency for the average total hazard in Palembang City to be in the low category. The value and probability of exceeding the occurrence of earthquakes with magnitudes greater or equal to the given price are estimated based on the Guttenberg-Ricther equation for earthquake catalog data which are mutually independent by applying regional b value and A value based on smoothing seismicity with a correlation distance of 25 km , 50 km, 75 km. Peak Ground Acceleration Value is estimated by applying several attenuation functions or often called Ground Motion Prediction Equation with input magnitude parameters and distance from the earthquake with the point of calculating the potential danger of earthquakes.